Incidence and Occurrence of Root-Knot Nematode (Meloidogyne species) in African Leafy Vegetables in Western Kenya - Mbogoh , J. M.; Omami , E.; Ngode , L.; Ochuodho , J. (African Journal of Education,Science and Technology (AJEST), 2013)
There is a rekindled interest and increased demand for African Leafy Vegetables (ALVs) by urban dwellers of all socio-economic classes in Kenya. The current supply of ALVs does not meet the domestic demand due to production constraints which include pests and diseases. Root knot nematodes (RKNs) are economically important pests in a wide range of cultivated vegetables in tropical and subtropical countries where they cause losses of up to 80% in heavily infested fields. However, there is little information on their incidence and occurrence on ALVs in Kenya. The study was conducted in Busia, Bungoma and Kakamega Counties in ALVs farms to determine the types of ALVs grown and the occurrence and prevalence of RKNs in Western Kenya. Structured questionnaires were administered to 120 purposively sampled respondents, 40 from each county. Soil samples from the farms and four most grown ALVs were sampled for RKNs presence and data analysed using SPSS. The study revealed that nine ALV types were grown in the three counties and the four most grown were Solanum nigrum (56%), Cleome gynandra (52%), Crotalaria spp. (46%) and Amaranthus spp. (45%). The frequency of RKN in the three counties ranged from 60-83% with Busia recording the lowest and Bungoma the highest. The incidence of RKN was highest in Solanum spp. (79.3%) as compared to Cleome spp. (10.7%), Crotalaria spp. (0.3%) and Amaranthus spp. (1%). The plant damage or root gall/root system of the plants differed significantly at P<0.05 for the four different ALVs; Solanum spp. (mean of 4.8), Cleome spp. (3.7), Crotalaria spp. (1.0) and Amaranthus spp. (2.5). Mixed cropping system was practiced by over 60% of the farmers with 48.3% of the farmers growing all their vegetables in the main farm, 80% in home gardens and 28.3% growing both in the main farm and in home gardens. RKNs prevalence was found to be high in the three counties at 73%. There was no significant difference in nematode levels both in mixed and mono cropping systems. Solanum was found to be very susceptible to RKNs while Crotalaria was a non-host.